Functional Theory: Origins, Influences and Principles Linked to the Arabic Linguistic Achievement - Almubarak , Mayada (Dirasat: Human and Social Sciences, 2024)
Objectives: Knowledge fields in other countries and languages are witnessing a strong trend towards linguistic sciences in all its varieties. Consequently, a number of scholars have taken an interest in studying these sciences, reflecting their significant theories and results, among which is the functional theory. Despite the extensive writings about this theory, some of its concepts, scope, limits, and its relationship with the Arab linguistic achievement appear unclear to many scholars. Hence, this research aims to study the functional theory, seeking to evaluate it from the Arab cognitive perspective and determine what Arabic requires from it. Methods: The research adopts a historical approach in tracing the origins of linguistic theories and their concepts, and an analytical approach in examining various concepts and terminologies. Results: There’s a need to review some corresponding functional concepts and terminologies in Arabic; such as the concept of prototypical adequacy, several pragmatic functions, and to benefit from the functional approach towards language teaching, semiotics, and translation. Conclusions: The study recommends a thorough examination of terminologies and general concepts. It emphasizes benefiting from the direction of linguistic theories, including the functional one, in focusing on translation, semiotics, and language teaching; by building computational, translational, and semiotic sciences based on the established Arabic rules.